Erodibility Parameters Derived from Jet and Flume Erosion Tests on Root‐Permeated Soils. (April 2017) - McNichol, Bailey; Kassa, Kayla; Fox, Garey; Miller, Ron; Guertault, Lucie
Abstract: Flume tests and in situ jet erosion tests (JETs) allow for the process‐based quantification of erodibility parameters of cohesive soils. In the excess shear stress model used to predict soil detachment, the critical shear stress (τ c ) corresponds to the stress at which fluvial forces can detach soil particles or aggregates and the erodibility coefficient ( k d ) governs the rate at which detachment occurs when the imposed shear exceeds τ c . The primary objective of this research was to derive and compare erodibility parameters from flume tests and JETs on various root‐permeated soil samples. Based on statistical analysis, erodibility coefficients from the flume tests were typically statistically similar to those derived with JETs. In order to further determine the capability of the JET to indicate differences in erodibility of root‐permeated soils, this research then performed JETs on side‐by‐side in situ soils. The JETs on root‐permeated soils estimated significantly higher τ c but insignificant differences in k d compared to JETs on adjacent bare soil. A significant correlation was observed between exposed root surface area (TRSA) and τ c, but no correlation between TRSA and k d or the equilibrium scour depth was observed. More flume and JET experiments are needed to clarify the relationship between root‐permeated soils and erodibility parameters, and address a wider range of average root diameters than was considered in this research.